Strategic targeting of development policies to a complex region: A GIS-based stratification applied to Uganda - Gerd Robert Ruecker; Soojin Park; Henry Ssali; John L. Pender (University of Bonn, Center for Development Research (ZEF), 2003)
It is often the case that national policies are not necessarily suitable at lower administrative levels due to the spatial complexity of natural and socio-economic resources within a country. That complexity of resources can be resolved by spatial modeling of natural and socio-economic variation. We propose a new GIS-based stratification algorithm to demarcate homogenous development domains at national level and applied that algorithm to Uganda. Based on that stratification, we assembled various spatial information to assess comparative advantages and disadvantages of these development domains for potential pathways of economic development. We expect that our stratification strategy may help policy makers and regional planners to target development investments more efficiently towards sustainable agriculture in Uganda.
Keywords: 330; International Development; Ländliche Entwicklungsplanung; Landwirtschaftliche Entwicklung; Agrargeographie; Standortfaktor; Uganda